Peningkatan Proses Pembelajaran Pendidikan Agama Islam Melalui Penerapan Model Kooperatif Tipe Jigsaw dengan Menggunakan Media Video Zakir Naik - Salamah, Salamah (BELAJEA: Jurnal Pendidikan Islam, 2019)
Islamic education faces several problems and challenges, one of the problems is that the portion of PAI hours at STIE Sakti Alam Kerinci is relatively small, which is 2 credits, so that it impacts on methodological problems, the learning strategy takes the form of lectures, because it is considered effective in overcoming time constraints i.e. lecturers explain while students hear and take notes. Not infrequently when given the opportunity to ask, not a student raised his hand to ask. This condition causes the class to be less dynamic and pleasant. This study aims to improve the process and results of Islamic Education using a cooperative type jigsaw model through video media Dr. Zakir Naik on STIE Sakti Alam Kerinci accounting study students. The population in this study were Accounting students in the even semester of the 2017/2018 academic year, totaling 90 people. In this study the author took only Accounting Class I which amounted to 45 people. Data collection is obtained through observation, interviews with students and documentation. The increase in the implementation of the Islamic Religious Education learning process using the jigsaw cooperative model through Zakir Naik's media in the first cycle, the second cycle and the third cycle became more enjoyable than before because students had new experiences, students who were less active became active during learning, student antusui seen when discussing.